Consumer Perceptions of a Shingles Infograph Intervention and Vaccination Plans in Community Pharmacy Settings - Radhika Devraj; Miranda Wilhelm; Maithili Deshpande (University of Minnesota Libraries Publishing, 2022)
Background: Cost and lack of knowledge are key barriers to improving shingles vaccination rates in community pharmacies. A health literacy (HL) tailored infograph intervention addressing these barriers can enhance consumer interest in shingles vaccinations.  Objectives: The objectives were to: 1) design a health literacy tailored shingles infograph addressing cost and knowledge about vaccination barriers, 2) determine consumer perceptions of infograph usefulness, and 3) determine factors associated with shingles vaccination plans. Methods: An infograph addressing the study objectives, and a 22-item self-administered questionnaire assessing shingles vaccine awareness, HL, infograph usefulness, and vaccination plans were designed. The infograph was pilot tested with pharmacists and two community-based focus groups. Inclusion criteria consisted of age-eligible consumers at one chain and three independent community pharmacies.  Consenting participants first reviewed the infograph and then completed the survey.  Descriptive statistics and multivariable logistic regression analyses were performed.  Results: Of the 422 eligible consumers approached, 112 participated in the study, with 55.4% from the chain pharmacies.  Participants were female (56%), white (94%), between 50-70 years old (77%), had adequate HL (96%) and aware of the shingles vaccine (87%).  While only 8% of the respondents considered vaccinating on the survey date, 46% considered it in the future, and 29% planned to in the next six months. The infograph was useful (90%) in recognizing vaccination need, was readable (95.5%), and understandable (96%).  Consumers who found the infograph useful were significantly more likely to have vaccination plans (OR= 4.06, CI: 1.37 - 11.9, p=0.016).  Conclusion: A shingles vaccine infograph focused on key barriers to vaccination was well-received and useful in promoting consumers' vaccination plans.